Exploring Cryptocurrency Perceptions and Its Global Conflict Resolution Concepts: Sentiment and Discourse Analysis - Alfina Rahmatia; Arief Dwi Saputra (Publication of the International Journal and Academic Research, 2025)
The intersection of cryptocurrency and international conflict resolution is a growing area of study, with many pressing questions about public conceptions and the constituent discourses of cryptocurrency in the context of global conflict. This paper will examine these perceptions using both sentiment and discourse analysis. Sentiment analysis uses R Studio on social media data, specifically Twitter, classifying public sentiment towards cryptocurrency, particularly Bitcoin, into three categories: positive, negative, and neutral. Meanwhile, parallel discourse analysis uses NVivo to examine the regular use of terms in research articles about cryptocurrency and its potential impact on conflict resolution. The qualitative review provides a deeper insight into the concepts that prompt public debate. The diversity of opinions will come forth in this research, as sentiment analysis will show the dominance of both positive and negative views. At the same time, discourse analysis will highlight the common themes of financial independence, regulatory barriers, and the ethical implications of using cryptocurrency in conflict situations. While some view cryptocurrencies as empowering more significant numbers of people and allowing the silenced to be heard, free from the constraints of mainstream institutions, others rise to point out the concerns of the volatile prices, potential for abuse, and lack of regulation to prevent abuse from taking place with these assets. This work adds to the increasing awareness related to how cryptocurrencies are seen to address international conflicts.